A qualitative study of patients’ coping strategies and expectations regarding spirituality during hospitalisation - Hairulisa @ Mohd Hairi, Nur Alia; Wan Mamat, Wan Hasliza; Mohamad Shariff, Nurasikin; Che Ahmad, Aminudin; Salah, Machouche; Jaafar, Siti Nur Illiani (IIUM Press, 2024)
Background: Hospitalisation can be a profoundly unsettling experience, often prompting patients to rely heavily on their spiritual beliefs and practices for comfort and strength. Spirituality, whether it involves prayer, meditation, reading religious texts, or other rituals, can provide significant psychological comfort and help patients navigate the emotional turmoil of their health challenges. The objective is to explore patients’ personal coping strategies and expectations regarding spirituality during hospitalisation. Methods: This study applied a phenomenological approach. Ten participants were recruited through purposive sampling. They participated in in-depth, face-to-face, and audio-recorded one-time interviews. All interviews were transcribed verbatim and analysed using thematic analysis to identify key themes. Results: Two themes were identified: (1) personal coping strategies with the subthemes: a) faith in God, b) reflection on family, and c) unleashing the power of self-motivation, and (2) Personal expectation with the subthemes: a) fostering attentiveness and empathy in patient care, and b) hospital management’s role. Conclusion: Patients seeking treatment in hospitals often need more than just physical medical interventions; their overall well-being can also significantly benefit from spiritual care. These findings suggesting hospital management teams to address staffing issues and enhance training programs to foster a more compassionate and patient-centric approach in patient care.